Comparative Analysis of Gulen Movement and Muhammadiyah: Their Internationalization Strategies and Integration with Governmental Systems - Muttaqien, Audi Izzat; Surwandono, Surwandono (Jurnal Hubungan Internasional, 2024)
This study examined how the Gulen movement and Muhammadiyah spread their influence to achieve their global vision and relations with the government. Both the Gulen movement and Muhammadiyah are Islamic-based non-governmental organizations and some of the largest in their respective countries and the world. This study employed a descriptive qualitative method to analyze the data and a literature study to collect the data. The analysis revealed that, first, by using the new transnational activism approach, the international role of the Gulen movement and Muhammadiyah brought benefits to both governments of origin. Muhammadiyah had a significant role in providing an excellent image for the Indonesian government. Meanwhile, despite the dispute and the Gulen movement’s independence, the public has viewed the movement as identical to a representative of the Turkish government with its international role and media use. Second, the approach of transnational Muslim NGOs has explained that both the Gulen movement and Muhammadiyah were oriented toward helping fellow Muslims with a focus on Muslim groups and countries. The Gulen movement built many educational institutions in Muslim-majority countries, such as Azerbaijan and Senegal. In contrast, Muhammadiyah accommodated and provided full scholarships for students from Muslim-majority areas, such as Southern Thailand and Mindanao, Phillippines. Muhammadiyah also helped mobilize humanitarian aid for Rohingya Muslims.